Effect of Moringa Leaf Iced Tea Consumption on Increasing Hemoglobin Levels in Adolescent Girls - Nisa, Ika Choirin; Nisa, Rif’atun (CV. Strata Persada Academia, 2025)
Anemia remains a significant public health issue among adolescent girls in Indonesia, primarily due to iron deficiency exacerbated by poor dietary habits and menstruation. Nutritional interventions utilizing local food sources such as Moringa oleifera offer a promising solution. Moringa leaves are rich in iron and essential micronutrients that may support hemoglobin synthesis. This study aims to examine the effect of Moringa leaf iced tea consumption on hemoglobin levels among adolescent girls. A quantitative pre-experimental design with a one-group pretest-posttest approach was employed. Ninety female students from a health sciences college in Cirebon participated. Hemoglobin levels were measured before and after the consumption of Moringa leaf iced tea. Data were analyzed using paired sample t-tests with a significance level of p < 0.05. The mean hemoglobin level increased significantly from 10.656 g/dL to 11.338 g/dL post-intervention, with a mean difference of 0.6822 g/dL (p < 0.001). This result suggests a positive hematinic effect of Moringa iced tea, likely due to its high iron and vitamin C content. Moringa leaf iced tea is a practical and culturally acceptable dietary intervention that effectively improves hemoglobin levels in adolescent girls. It holds potential for integration into school and community-based nutrition programs aimed at preventing anemia.